Analysis of the Relationship Between the Market Structure and Performance: a Case Study of the Insurance Industry in Algeria - Snoussi, Oussama; Mahboub, Fatima (Finance and Business Economies Review, 2020)
This study aims at analyzing the relationship between market structure and the performance of the insurance companies in Algeria's property and casualty insurance market by adopting the model of analysis in the industrial organization (SCP); (Structure-Conduct-Performance). Moreover, the study is based on the hypothesis of existence of a Mutual Influence between market structure and performance. Accordingly, the study sample is included ten insurance companies during the period between 2007 and 2015. A simultaneous equation is employed to estimate the parameters of the model, relying on Two-Stage Least Square (2SLS) and Three-Stage Least Square. On the whole, the study concludes that Algeria's property and casualty insurance market is characterized by a monopoly structure and heading towards competition, the study also dictates the existence of impact between the structure of the insurance market and the performance of insurance companies operating in it, this effect is negative between the two variables in both directions, which means rejection of the structure-Conduct-performance paradigm hypothesis, that is, public insurance companies that control the insurance market do not benefit from the dominant position in making unusual profits, and they are far from monopolistic behaviors